The first network of marine protected areas (MPAs) in the high seas: The process, the challenges and where next - O'Leary, B.C.; Brown, R.L.; Johnson, D.E.; von Nordheim, H.; Ardron, J.; Packeiser, T.; Roberts, C.M. (Marine policy, 2012)
Marine protected areas (MPAs) are increasingly being established to protect and rebuild coastal and marine ecosystems. However, while the high seas are increasingly subject to exploitation, globally few MPAs exist in areas beyond national jurisdiction. In 2010 a substantial step forward was made in the protection of high seas ecosystems with 286,200km2 of the North-East Atlantic established as six MPAs. Here a summary is presented of how the world's first network of high seas marine protected areas was created under the OSPAR Convention, the main challenges and a series of key lessons learned, aiming to highlight approaches that also may be effective for similar efforts in the future. It is concluded that the designation of these six MPAs is just the start of the process and to achieve ecological coherence and representativity in the North-East Atlantic, the network will have to be complemented over time by additional MPA sites. ► In 2010 the world's first network of high seas MPAs was created in the NE Atlantic. ► 286,200km2 of high seas was protected in 6 MPAs under the OSPAR Convention. ► Many scientific, legal and political challenges had to be overcome. ► 11 key lessons learned which may aid similar efforts elsewhere are emphasised. ► Designation is concluded to be only the beginning and many challenges lie ahead.